5(x+6)=3(x-4)

Simple and best practice solution for 5(x+6)=3(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+6)=3(x-4) equation:



5(x+6)=3(x-4)
We move all terms to the left:
5(x+6)-(3(x-4))=0
We multiply parentheses
5x-(3(x-4))+30=0
We calculate terms in parentheses: -(3(x-4)), so:
3(x-4)
We multiply parentheses
3x-12
Back to the equation:
-(3x-12)
We get rid of parentheses
5x-3x+12+30=0
We add all the numbers together, and all the variables
2x+42=0
We move all terms containing x to the left, all other terms to the right
2x=-42
x=-42/2
x=-21

See similar equations:

| A=2x+24x+46 | | 7w+40=12w | | 4.3+10m=7.51 | | 208=85-u | | 8x²+16x+1=0 | | 4+b2=49 | | c/4+40=45 | | 100x+20(2x+6)+50Y=3560 | | -j+23=-5 | | -(1-5v)=-9+5v | | 9X-5y=2800 | | -1(-5v)=-9+5v | | -0.9-5.5b+0.1=-5.7b+0.88 | | r-6.7=17 | | 157.90=(0.05m+24.80+0.10(24.80) | | 6=14x-8x | | 24x+124=180 | | 2(2n-2)=4n-4 | | -(-5x+1)=-6+4x | | -5a+5a=4 | | --3.6h=-10.8 | | 6(4+2k)=3(k+8) | | 17+13d=43 | | −5.6x=−4 | | 3k+6-7=-6k+2k-15 | | 6.4g+9=4.4g+13 | | c+4=-3c-20 | | 6+3(4n+5)=29+8n | | 5n-3=-5+7n | | 4(8x+6)-3(x-7)=-42 | | -2+4(1+6x)=146 | | X.2x=100 |

Equations solver categories